The greenwashing trap: how misleading marketing affects consumer green purchasing habits - Vilkaitė-Vaitonė, Neringa (Business: Theory and Practice, 2024)
The rising environmental concern has driven organizations to adopt green marketing practices. However, a growing number of organizations have been engaging in greenwashing practices, which mislead customers about their environmental performance. This can have negative consequences for the organization, the industry, and society as a whole. Despite the growing concern about greenwashing, there is limited research on how it affects consumers’ purchasing decisions. To address this gap, we conducted a study to explore the effect of greenwashing perception on green purchase intention in the touristic accommodation industry. Primary data was collected from 693 tourists who visited the Canary Islands, and structural equation modeling (SEM) was used to verify hypotheses with the help of AMOS 29 software. The findings revealed that greenwashing perception does not directly affect green purchasing intention or impact green trust. However, green trust was found to be a significant predictor of sustainable choices in the touristic accommodation industry. Additionally, the study provided evidence that previous touristic accommodation experience moderates the relationship between green trust and green purchase intention and the relationship between greenwashing perception and green trust. This research has important implications for marketers and adds to the body of knowledge on greenwashing and green purchasing. By incorporating the Stimulus-Organism-Response (SOR) paradigm, this study uncovers new linkages that better help understand the phenomenon of green purchasing among travelers.